2018
DOI: 10.1111/sji.12707
|View full text |Cite
|
Sign up to set email alerts
|

Patients with out‐of‐hospital cardiac arrest show decreased human leucocyte antigen‐DR expression on monocytes and B and T lymphocytes after return of spontaneous circulation

Abstract: Immune disorders are an important feature of patients with out‐of‐hospital cardiac arrest (OHCA) after return of spontaneous circulation (ROSC). However, the precise immune alterations in patients with OHCA that occur immediately after ROSC are unclear. In this study, we investigated human leucocyte antigen‐DR (HLA‐DR) expression on circulatory monocytes and B and T lymphocytes. Sixty‐eight consecutive patients with OHCA with ROSC >12 hours were enrolled. Clinical data and 28‐day survival were recorded. Periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
1
4
0
1
Order By: Relevance
“…This study strengthens the hypothesis that resuscitated patients develop early immunoparalysis, which can be characterized by downregulation of mHLA-DR expression, as previously demonstrated 32 34 . However, this is the first study to show that HLA-DR expression is altered primarily among classical monocytes.…”
Section: Discussionsupporting
confidence: 91%
“…This study strengthens the hypothesis that resuscitated patients develop early immunoparalysis, which can be characterized by downregulation of mHLA-DR expression, as previously demonstrated 32 34 . However, this is the first study to show that HLA-DR expression is altered primarily among classical monocytes.…”
Section: Discussionsupporting
confidence: 91%
“…L -1 olarak saptadıklarını ve SDGD sağlanan olgularda yüksek BK değerlerinin istatistiksel olarak anlamlı olduğunu bildirmişlerdir (16) . KA olgularında yapılan KPR'nin, iskemi/reperfüzyon hasarı nedeniyle sepsis benzeri sendroma ve immün sistem ile ilgili bozuklukların aktivasyonuna neden olur (17) . BK; granülositler ve non granülositler olmak üzere 2 ana grupta değerlendirilir.…”
Section: Bulgularunclassified
“…However, no study has reported the GR expression after ROSC in patients who experienced CA. Previous studies have found that the counts of circulating B and T lymphocytes, regulatory T (Treg) cells and monocytes and expression of human leucocyte antigen DR on circulatory monocytes and B and T lymphocytes are reduced 23 24. Hence, this study aimed to investigate the relationship between GR expression and immune alteration in the early period after ROSC in patients who experienced CA by observing GR expression in circulatory T and B lymphocytes, natural killer (NK) cells and Treg cells, their cell counts, and total plasma cortisol and adrenocorticotrophic hormone (ACTH) levels.…”
Section: Introductionmentioning
confidence: 99%